Longitudinal characterization of primary osteosarcoma and derived subcutaneous and orthotopic relapsed patient-derived xenograft models - da Costa, Maria Eugenia Marques; Droit, Robin; Khneisser, Pierre; Gomez-Brouchet, Anne; Adam-de-Beaumais, Tiphaine; Nolla, Marie; Signolles, Nicolas; Torrejon, Jacob; Lombard, Bérangère; Loew, Damarys; Ayrault, Olivier; Scoazec, Jean-Yves; et al. (Frontiers in Oncology, 2023)
Osteosarcoma is a rare bone cancer in adolescents and young adults with dismal prognosis because of metastatic disease and chemoresistance. Despite multiple clinical trials, no improvement of outcome has occurred in decades. There is an urgent need to better understand the resistant and metastatic disease and to generate in vivo models from relapsed tumors. We developed eight new patient-derived xenograft (PDX) subcutaneous and orthotopic/paratibial models derived from patients with recurrent osteosarcoma and compared the genetic and transcriptomic landscapes of the disease progression at diagnosis and relapse and the matching PDX. Whole exome sequencing showed that driver and copy-number alterations are conserved from diagnosis to relapse, with the emergence of somatic alterations of genes mostly involved in DNA repair, cell cycle checkpoint and chromosome organization. All PDX conserve most of the genetic alterations identified at relapse. At the transcriptomic level, tumor cells maintain their ossification, chondrocytic and trans-differentiation program during progression and implantation in PDX models, identified at the radiological and histological level. A more complex phenotype like the interaction with immune cells and osteoclasts or cancer testis antigen expression seemed conserved and was hardly identifiable by histology. Four of the PDX models reconstructed partially the vascular and immune-microenvironment observed in patients, among which, the macrophagic TREM2/TYROBP axis expression, recently linked to immunosuppression, and those despite NSG mice immunodeficiency. Our multimodal analysis of osteosarcoma progression and PDX models are precious resources to understand resistance and metastatic spread mechanisms, as well as for exploration of novel therapeutic strategies for advanced osteosarcoma.